A MODEL FOR CONCEPTUALIZING THE KNOWLEDGE IN SUPPLY CHAIN RELATIONSHIPS. CASE STUDY: MANUFACTURING SMEs IN THE - Oscar Montano Arango; Jose Ramon Corona Armenta; Israel Aaron Palma Quiroz; Jaime Garnica Gonzalez; Marco Antonio Montufar Benitez; Hector Rivera Gomez (European Scientific Journal, ESJ, 2014)
We present a conceptual model between the relations of knowledge in small and medium-sized manufacturing enterprises and their supply chains in the State of Hidalgo, Mexico. It is structured according to the dynamics of their environment, features internal this type of organizations and different models identified in the literature, being the premise identification and analysis capabilities of the processes that shape enterprise and chaining with their suppliers and customers.